Answer:
[tex]\int^1_0\int^3_0\int^9_{3y}\frac{6 cos x^2}{5\sqrt z}dxdydz[/tex] [tex]=\frac{18}{5}(1+\frac{sin2}{2})[/tex]
Step-by-step explanation:
cosine x²= cos x²
Rule
Given that,
[tex]\int^1_0\int^3_0\int^9_{3y}\frac{6 cos x^2}{5\sqrt z}dxdydz[/tex]
[tex]=\int ^1_0[\int^3_0(\int^9_{3y} \frac{6cos x^2}{5\sqrt z}dz)dy]dz[/tex]
[tex]=\int^1_0[\int^3_0([\frac{6cos x^2 \times \sqrt z}{5\times \frac{1}{2}}]^9_{3y})dy]dx[/tex]
[tex]=\int^1_0[\int^3_0([\frac{12cos x^2 \times( \sqrt 9-\sqrt{3y})}{5}])dy]dx[/tex]
[tex]=\int^1_0[\int^3_0([\frac{12cos x^2 \times( 3-\sqrt{3y})}{5}])dy]dx[/tex]
[tex]=\int^1_0[\frac{12cos x^2 \times( 3y-\frac{\sqrt{3}y^\frac{3}{2}}{\frac{3}{2}})}{5}]^3_0dx[/tex]
[tex]=\int^1_0[\frac{12cos x^2 \times( 3.3-\frac{2\sqrt{3}.3^\frac{3}{2}}{3})}{5}]^3_0dx[/tex]
[tex]=\int^1_0[\frac{12cos x^2 \times( 9-6)}{5}]dx[/tex]
[tex]=\frac{18}{5}\int^1_02cos x^2dx[/tex]
[tex]=\frac{18}{5}\int^1_0(1+cos2x)dx[/tex]
[tex]=\frac{18}{5}[(x+\frac{sin2x}{2})]^1_0[/tex]
[tex]=\frac{18}{5}(1+\frac{sin2}{2})[/tex]